Ultraviolet-B and water stress effects on growth, gas exchange and oxidative stress in sunflower plants - Cechin, Inês [UNESP]; Corniani, Natalia [UNESP]; Fumis, Terezinha de Fátima [UNESP]; Cataneo, Ana Catarina [UNESP] (Springer, 2008)
The effects and interaction of drought and UV-B radiation were studied in sunflower plants (Helianthus annuus L. var. Catissol-01), growing in a greenhouse under natural photoperiod conditions. The plants received approximately 1.7 W m(-2) (controls) or 8.6 W m(-2) (+UV-B) of UV-B radiation for 7 h per day. The UV-B and water stress treatments started 18 days after sowing. After a period of 12 days of stress, half of the water-stressed plants (including both UV-B irradiated or non-irradiated) were rehydrated. Both drought and UV-B radiation treatments resulted in lower shoot dry matter per plant, but there was no significant interaction between the two treatments. Water stress and UV-B radiation reduced photosynthesis, stomatal conductance and transpiration. However, the amplitude of the effects of both stressors was dependent on the interactions. This resulted in alleviation of the negative effect of drought on photosynthesis and transpiration by UV-B radiation as the water stress intensified. Intercelluar CO(2) concentration was initially reduced in all treatments compared to control plants but it increased with time. Photosynthetic pigments were not affected by UV-B radiation. Water stress reduced photosynthetic pigments only under high UV-B radiation. The decrease was more accentuated for chlorophyll a than for chlorophyll b. As a measure for the maximum efficiency of photosystem II in darkness F (v)/F (m) was used, which was not affected by drought stress but initially reduced by UV-B radiation. Independent of water supply, UV-B radiation increased the activity of pirogalol peroxidase and did not increase the level of malondialdehyde. on the other hand, water stress did not alter the activity of pirogalol peroxidase and caused membrane damage as assessed by lipid peroxidation. The application of UV-B radiation together with drought seemed to have a protective effect by lowering the intensity of lipid peroxidation caused by water stress. The content of proline was not affected by UV-B radiation but was increased by water stress under both low and high UV-B radiation. After 24 h of rehydration, most of the parameters analyzed recovered to the same level as the unstressed plants.